The alchemist : a fable about following your dream - Coelho, Paulo (HarperPerennial, 1998)
An Andalusian shepherd boy named Santiago travels from his homeland in Spain to the Egyptian desert in search of a treasure buried in the Pyramids. Along the way he meets a Gypsy woman, a man who calls himself king, and an alchemist, all of whom point Santiago in the direction of his quest. No one knows what the treasure is, or if Santiago will be able to surmount the obstacles along the way. But what starts out as a journey to find worldly goods turns into a discovery of the treasures found within.